Understanding Teachers’ Intentions and Use of AI Tools for Research - Kriti Priya Gupta (Je-LKS: Journal of E-Learning and Knowledge Society)
The rapid advancement of artificial intelligence (AI) has led to the development of a wide array of tools which are transforming the education industry. The study investigates the adoption and use of AI tools by teachers within higher education institutions (HEIs), using the context of India. By employing an extended Unified Theory of Acceptance and Use of Technology (UTAUT) model, the study empirically examines the influence of two technological attributes (i.e. performance expectancy and effort expectancy), two contextual factors (i.e. social influence and facilitating conditions) and two personal characteristics (i.e. personal innovativeness and computer self-efficacy) on teachers’ behavioural intention to use AI tools for research work. The primary data were collected from 331 teachers working with HEIs in the Delhi-National Capital Region (NCR) of India. PLS-SEM technique was used to analyze the data. The findings indicate that teachers’ intention to adopt AI tools for research work is positively influenced by performance expectancy, effort expectancy, social influence, computer self-efficacy and personal innovativeness. Further, their actual use of AI tools is influenced by their behavioural intention and facilitating conditions. The study provides further verification of the effectiveness of the UTAUT framework in the context of using emerging technologies in the education sector. Findings from this study provide beneficial insights for HEIs and developers of AI tools.